2013
DOI: 10.1007/s11259-013-9579-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of innate immune response following in vitro stimulation of sheep and goat peripheral blood mononuclear cells with bluetongue virus – serotype 23

Abstract: Bluetongue is an infectious disease caused by bluetongue virus (BTV), which affects sheep, goat, cattle and certain wild ruminants. However severe clinical signs are usually seen with significant mortality in sheep than cattle and goat. To date, comparative studies on innate immune responses of sheep and goat infected with BTV is lacking. In this study, we compared the innate immune response of sheep and goat by infecting the peripheral blood mononuclear cells (PBMCs) with BTV serotype 23. In our study, we obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Antibodies to the virus (BTV) are common in cattle, buffaloes and goats, but the clinical disease has not been reported in these animals [24]. Recently, the RNA levels of the BTV in the PBMC culture supernatant showed, sheep PBMCs supports more replication of the virus compared to goats [18]. However, the severity of the disease in the sensitive hosts depends on the strain of the virus, breed, immune status of the animal, virulence of the virus, other host factors etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibodies to the virus (BTV) are common in cattle, buffaloes and goats, but the clinical disease has not been reported in these animals [24]. Recently, the RNA levels of the BTV in the PBMC culture supernatant showed, sheep PBMCs supports more replication of the virus compared to goats [18]. However, the severity of the disease in the sensitive hosts depends on the strain of the virus, breed, immune status of the animal, virulence of the virus, other host factors etc.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the viral pathogenesis of BTV resulting in presence or absence of clinical disease among different hosts is not clearly understood and both, the virus and host species are thought to be of importance. PBMCs were used in vitro to study the innate immune responses in sheep and goats in response to BTV infection [18]. Recently, global transcriptome analysis was used to understand the molecular events of host virus interactome in PPRV [19], Measles virus [20], [21] and Rinderpest virus [21] infections.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in vitro BTV infections of peripheral blood mononuclear cells (PBMC) from a number of ruminant species resulted in the production of inflammatory cytokines. BTV infection of PBMC from bovine 39, sheep and goats 41 induced IL-1, 6, 8, and 10, IFN-γ, TNF and iNOS, although these studies used different experimental designs and BTV serotypes, making correlations among species difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Together with its ability to modulate IFN synthesis (38), BTV would then ensure a powerful inhibition of the cellular response. Several studies have suggested that IFN-I is an important factor to limit BTV replication and dissemination and control infection (52)(53)(54). By inhibiting both IFN-I synthesis and signaling pathways, BTV would then promote the establishment of an infection.…”
Section: Discussionmentioning
confidence: 99%